Ultrazvočno vodeno dreniranje plevralnega prostora - Štupnik, Tomaž (Zdravniški vestnik, 2008)
Background Chest ultrasound (US) is well documented as a valuable tool for pleural diseases. US helps to clarify the cause of pleural opacities, estimatethe volume of pleural effusion and identify minimal or loculated pleural effusion. US characteristics of effusion provide helpful information regarding the nature of the effusion. Pleural diseases, such as pleural fibrosis, tumours and pneumothorax all display different diagnostic US features. Safe thoracentesis and drainage of effusion can be carried out underUS guidance with a high success rate. The technique of US, which is safe and cost-effective compared to CT scanning, may be learned relatively easily by the pulmonologist and thoracic or general surgeons. Conclusions US guidanceis recommended for every chest tube insertion, especially in the ICU patients. Appropriate US machine should be readily available in every trauma, ICU, pulmonology and thoracic surgery unit.
Keywords: Chest Tubes; diagnostika; Empiem prevralni; Empyema, Pleural; Hematotoraks; Hemothorax; Pleural Effusion; Plevralni izliv; prsni koš; Prsni koš, tubusi; therapy; Thoracotomy; Torakotomija; Ultrasonography; ultrasound; ultrazvok; zdravljenje